Assessing Alternative Scenarios for the Cause of Underpressures in the Ordovician Sediments along the Eastern Flank of the Michigan Basin. (10th December 2017) - Normani, Stefano D.; Sykes, Jonathan F.; Jensen, Mark R.; Sykes, Eric A.
Abstract : Geoscientific investigations for a proposed deep geologic repository at the Bruce Site, located on the eastern flank of the Michigan Basin, have identified unique and significant underpressured conditions. Along with the measurement of environmental tracer profiles (e.g., helium), this study aims to explore, through a series of numerical simulations, the nature of long-term phenomena responsible for the generation and preservation of formation underpressures. Three families of inverse numerical experiments for underpressure formation were examined by means of one-dimensional hydromechanically coupled models through the vertical hydrostratigraphic column: (i) uncertainty in glaciation scenarios; (ii) uncertainty in initial heads prior to glaciation; and (iii) uncertainty in the degree of hydraulic connectivity between the more permeable Guelph Formation at the Bruce Site and the applied glacial loading, for a total of 20 scenarios, assuming fully saturated conditions. Underpressured initial heads for the paleohydrogeologic simulations lead to lower calibrated vertical hydraulic conductivities. The robustness and resilience of the groundwater system to external perturbations are greater for the state where underpressured conditions predate the onset of glaciation and are better able to preserve the present day helium tracer profile in 260 Ma exhumation analyses.